2015
DOI: 10.1515/jhsem-2014-0086
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Risk Communication Gaps through E-Government Website and Twitter Hashtag Content Analyses: The Case of Indonesia’s Mt. Sinabung Eruption

Abstract: Despite operational volcano surveillance using meteorological satellite, thermal remote sensing and infrared camera technologies, predicting a volcano's hazardous activity and explosive eruption, with any accuracy, remains nearly impossible. Volcanic hazards and risk literature identifies risk communication as critical but insufficiently understood. This paper, therefore, investigates disaster risk communications during Indonesia's Mt. Sinabung eruptions in February 2014, causing 16 deaths and continuous evacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Citizen-centric model of governmental entrepreneurship developed by Kumar (2019) does highlight the importance of public sector governance for better social program outcomes at the same time-solving issues of bureaucratic hurdles and leverage the untapped capabilities of the marginalized citizen. Chatfield and Reddick (2015) found that social media (in this case, Twitter) can be a governance platform between public agencies and act as a multi-directional risk communication tool to quickly and effectively share risk perceptions and disaster information with the public. Thus, it is crucially important to have management support from leaders, shared goals, and inter-organizational trust in performing cross-boundary government system (Chen et al, 2019).…”
Section: Governancementioning
confidence: 99%
“…Citizen-centric model of governmental entrepreneurship developed by Kumar (2019) does highlight the importance of public sector governance for better social program outcomes at the same time-solving issues of bureaucratic hurdles and leverage the untapped capabilities of the marginalized citizen. Chatfield and Reddick (2015) found that social media (in this case, Twitter) can be a governance platform between public agencies and act as a multi-directional risk communication tool to quickly and effectively share risk perceptions and disaster information with the public. Thus, it is crucially important to have management support from leaders, shared goals, and inter-organizational trust in performing cross-boundary government system (Chen et al, 2019).…”
Section: Governancementioning
confidence: 99%
“…In addition to allowing organizations, both public and private, to use Twitter as a platform to disseminate information, the platform can also facilitate multidirectional communication. It creates a fast and effective channel of communication between government organizations, related agencies, communities, and society at large, resulting in the creation of a channel for sharing disaster information and risk perceptions with the public (Chatfield & Reddick, ). The ability for Twitter to assist in reducing the impact of a disaster by efficiently providing individuals with reliable information serves as a key need for this research.…”
Section: Disaster Managementmentioning
confidence: 99%
“…The public sector makes use of Twitter for a number of reasons, such as stakeholder communication and the sharing of information (McInnes & Hornmoen, ), calls to action (Al‐Aama, ), networking (Gao, ; Khan, Yoon, Kim, & Park, ), citizen engagement (Haro‐de‐Rosario, Sáez‐Martín, & del Carmen Caba‐Pérez, ), or disaster management (Chatfield & Reddick, ). Another study by Eom, Hwang, and Kim () shows that Twitter can enhance public service and improve government responsiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Twitter-based information for communication of a volcanic eruption, Indonesia's Mt. Sinabung, was also analyzed by Chat eld and Reddick [236]. A Big Data Assimilation (BDA) project was described by Miyoshi et al [237] for weather prediction, providing an early warning about natural disasters such as tornadoes and oods, among others.…”
Section: Big Data and Natural Disastersmentioning
confidence: 99%